Pediatric out-of-hospital deaths following hospital discharge - English, Lacey; Kumbakumba, Elias; Larson, Charles P; Kabakyenga, Jerome; Singer, Joel; Kissoon, Niranjan; Ansermino, J Mark; Wong, Hubert; Kiwanuka, Julius; Wiens, MO (African Health Sciences, 2016)
Background: Out-of-hospital death among children living in resource poor settings occurs frequently. Little is known about the location and circumstances of child death following a hospital discharge. Objectives: This study aimed to understand the context surrounding out-of-hospital deaths and the barriers to accessing timely care for Ugandan children recently discharged from the hospital. Methods: This was a mixed-methods sub-study within a larger cohort study of post-discharge mortality conducted in the Southwestern region of Uganda. Children admitted with an infectious illness were eligible for enrollment in the cohort study, and then followed for six months after discharge. Caregivers of children who died outside of the hospital during the six month post-discharge period were eligible to participate in this sub-study. Qualitative interviews and univariate logistic regression were conducted to determine predictors of out-of-hospital deaths. Results: Of 1,242 children discharged, 61 died during the six month post-discharge period, with most (n=40, 66%) dying out side of a hospital. Incremental increases in maternal education were associated with lower odds of out-of-hospital death compared to hospital death (OR: 0.38, 95% CI: 0.19 – 0.81). The qualitative analysis identified health seeking behaviors and common barriers within the post-discharge period which delayed care seeking prior to death. For recently discharged children, caregivers often expressed hesitancy to seek care following a recent episode of hospitalization. Conclusion: Mortality following discharge often occurs outside of a hospital context. In addition to resource limitations, the health knowledge and perceptions of caregivers can be influential to timely access to care. Interventions to decrease child mortality must consider barriers to health seeking among children following hospital discharge.
A mixed-methods study.
Keywords: Pediatrics; post-discharge mortality; Uganda; qualitative interviews; infectious diseas.